Os meios de aprendizagem empreendedora e a formação de competências empreendedoras em mulheres que atuam na economia informal - Maciel, Jéssica da Silva (2021)
The definition of informal economy encompasses self-employed workers, in activities for their own survival, such as street vendors, homeworkers, self-employed in self-employed micro-businesses, etc. (ILO, 2002). In the informal economy, according to the ILO (2018) there are more than 740 million women entrepreneurs. The growth in the number of women in entrepreneurial activities is significant, so that studies on the theme become increasingly relevant; in this sense, the study of female informal entrepreneurship is an important field of research, due to the scope of the informal economy and also the diffusion of female entrepreneurship in this context. In addition, studies on female entrepreneurship in Brazil are incipient, which reinforces the importance of conducting this research that brings to light relevant reflections on the female entrepreneurial trajectory in the informal economy. Thus, the objective of this research is to analyze how entrepreneurial trajectories stimulate learning and the development of Entrepreneurial Skills in women working in the Brazilian Informal Economy. In order to achieve the proposed objectives, the study adopted a qualitative and exploratory methodological approach, conducting semi-structured interviews with eight Women Entrepreneurs of the Informal Economy. The results point out the challenges and opportunities inherent to entrepreneurial activity in this segment, as well as the motivations that guide the decision to undertake. In addition, the main entrepreneurial skills identified in the women interviewed and the means of learning in the formation of these skills are listed. The reasons that led to the entry into the Informal Economy are varied, with an emphasis on dissatisfaction with the conditions of previous jobs, associated with the search for a job with purpose and ecological consciousness, opposing to the idea that entry into the informal economy occurs by necessity. Among the main entrepreneurial skills of the women studied, adaptability stood out. Regarding the Entrepreneurial Learning Means most present in the interviewees' trajectory, learning in practice, experimentation and the active search for knowledge emerged. In addition, the study brings a reflection on how entrepreneurial activity is viewed in the family context, showing differences about family support for female entrepreneurs who have their business as a priority source of income and those who have other work activities in addition to their business. The study's limitations include the number of women interviewed and the non-use of other data sources. For future studies, it is suggested to expand the interviews, including other data collection techniques such as participant observation, for example. The main contributions of the study are aimed at expanding the theoretical framework about female informal entrepreneurship in Brazil, also serving as a basis for proposing public policies that aim to help women in this context.